Behaviour and reproduction of Drosophila melanogaster exposed to 3.6 GHz radio-frequency electromagnetic fields - Pieterjan De Boose; Felipe Oliveira Ribas; Duncan Bell; Maria Bouga; Eline De Borre; Jürg Fröhlich; Fani Hatjina; Anke Huss; Anastasia Kalapouti; Orestis L. Katsamenis; Lewis Blackwell; Pantelitsa Georgiadou; et al. (PLoS ONE, 2025)
Insects are exposed to radio-frequency electromagnetic fields emitted by wireless telecommunication networks. A part of these fields will be absorbed by these insects. This absorption might have biological effects, depending on the amount of absorbed power. It is currently unknown at what level of absorption this might occur. To investigate this, we used RF dosimetry of adult Drosophila melanogaster flies, which we combined with two assays studying the locomotor activity and fecundity of D. melanogaster exposed to electromagnetic fields at 3.6 GHz. To perform dosimetry, we created a 3D digital twin of an adult fly using micro-CT scans of a female D. melanogaster . We used this model in numerical EM simulations to estimate the absorbed power in the fly as a function of RF frequency in the far field of an antenna and during the two experimental assays at 3.6 GHz. In the behavioural experiments, no effects were found on the locomotor activity for a 5-day exposure to RF field values between 5.4 and 9 V/m, which correspond to 3.56 nW to 9.88 nW absorbed power. We also did not find any effects on fecundity, at an absorption level of 1.91 mW for 48h at 3.6 GHz. In our future work, we aim to investigate possible exposure effects at higher frequencies and exposures, and for immature stages.